Influence of harvesting factors on sensory attributes and phenolic and aroma compounds composition of Cymbopogon citratus leaves infusions. (November 2016) - Coelho, M.; Rocha, C.; Cunha, L.M.; Cardoso, L.; Alves, L.; Lima, R.C.; Pereira, M.J.; Campos, F.M.; Pintado, M.
Abstract: Herbal infusions are receiving increasing attention for the number of physiological benefits that can bring to human health. Cymbopogon citratus is one the most used plants in traditional medicine besides its characteristics and unique aroma appreciated by the consumers; however, little is known about the effects of harvesting on functional and sensory properties of this plant. The present work aimed to assess the lemongrass infusions, which were harvested following a factorial plan according to the type of cut (manual and mechanical) and part of the plant (tips and 2nd half leaves). Total phenolic content, antioxidant capacity, aroma compounds composition (terpenoids) and sensory profiles and consumer perception of different samples were assessed. The quantitative descriptive analysis (QDA) and Check-All-That-Apply (CATA) methods were used to describe the lemongrass infusion, complemented with the overall liking evaluation, using a 9-point scale. Results showed that there were significant differences between type of cut and part of the plant concerning phenolic compounds: samples obtained by mechanical cut showed in general higher content of individual phenolic compounds (in particular for chlorogenic acid) and tips showed in general the highest contents for both types of cut. Consumers panel did not found significant differences between samples. Generally, consumers indicate a bitter taste in all infusions when the content of the phenolic compounds was higher, in particular for p-coumaric acid. Concerning the aroma compounds no significant differences were observed between type of cut and part of the plant, and citral was the terpenoid present in higher quantity. Regarding the sensory profile methods, it was found that QDA and CATA were both good methods to describe this infusion. Considering the role of consumers' evaluation throughout the value chain, the infusion prepared with plant tips of lemongrass was selected as the premium herbal tea. Graphical abstract: Highlights: Influence of harvesting conditions in sensory, phenolic and aroma properties Association of phenolic compounds with bitterness in sensory perception Cymbopogon citratus harvested from tips of the plant yielded premium infusions.